Determinants of intention to use e-wallet in Generation Z - Rahmadhani, Safitri Dwi; Buchdadi, Agung Dharmawan; Fawaiq, Muhammad; Prasetya, Budi Agung (BISMA (Bisnis dan Manajemen), 2023)
Generation Z, as true digital natives or generations born and raised with the internet, is familiar with digital products. One digital product is an e-wallet used as an online payment method. This study aims to discover the factors that influence behavioural intention to use e-wallets in generation Z that use an e-wallet and live in Greater Jakarta. The theoretical basis of this study is the Technology Acceptance Model (TAM), where the variables involved are behavioural intention to use, perceived ease of use, and perceived usefulness, and two other factors, i.e., perceived security and social influence. A total of 245 respondents were collected by online survey and analysed with Structural Equation Modelling (SEM). This study finds that social influence affects perceived ease of use positively and significantly. Perceived ease of use influences perceived usefulness positively and significantly. Perceived ease of use and perceived usefulness positively influence behavioural intention to use. However, social influence does not influence perceived usefulness, and perceived security does not influence behavioural intention to use. This study's originality resides in its examination of reported ease of use and perceived usefulness as mediating variables of social influence on Generation Z's propensity to use e-wallets.